CLINICAL CASES OF LATE DIAGNOSIS OF MALIGNANT LYMPHADENOPATHY IN CHILDREN AND ADOLESCENTS - Григорий Михайлович Сергиенко; Марина Михайловна Котович; Марина Юрьевна Горошкова; Елена Петровна Шабашкевич; Наталья Владимировна Селиванова (The Publishing House Medicine and Enlightenment, 2022)
Lymph node enlargement syndrome in children and adolescents is one of the most frequent reasons for seeking medical care worldwide. We present clinical cases of difficult diagnosis of LAP. Objective of the study - to analyze clinical cases of late diagnosis of malignant lymphadenopathy. Materials and Methods. We analyzed 47 histories of patients aged 0 to 18 years who were admitted to the hospital with a provisional diagnosis of lymphadenopathy between January 2018 and June 2022. Results. The most frequently observed lymph node enlargement in the cervical and submandibular regions was 1.1 to 2.5 cm. Enlarged supraclavicular and/or subclavian lymph nodes were associated with cancer in 100 % of cases. The median age of patients with malignant lymphadenopathies was 12 years. Boys predominated, 61.5 % versus 38.5 % of girls. The period from the detection of symptoms to hospitalization was long and was 1.5 months. Conclusion. In children, lymphadenopathy is most often reactive. Detection of enlarged lymph nodes in children older than 10 years old requires inclusion of cancer in the circle of differential diagnosis.